Novel targeted therapy and cellular immunotherapy enabling allogeneic hematopoietic stem cell transplantation for relapsed/refractory acute myeloid leukemia - Liqin Cao; Daihong Hu; Lijuan Cui; Xiaohui Zhang (Chinese Medical Journal, 2026)
Abstract Patients with relapsed or refractory (R/R) acute myeloid leukemia (AML) are characterized by a disastrous prognosis. For most patients with R/R AML, allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative option. It is important to conduct mutational analysis again when the disease relapses to identify any new genetic abnormalities that can be targeted with novel treatments. As part of a conditioning regimen or post-transplant maintenance therapy, new targeted agents support HSCT in patients with R/R AML in various forms, including combination chemotherapy to improve complete remission (CR) prior to HSCT. For R/R AML patients with mutated FMS-related tyrosine kinase 3 ( FLT3 ), sorafenib and quizartinib have shown encouraging therapeutic effects either in combination with chemotherapy for bridging to transplantation or as maintenance therapy after HSCT. Ivosidenib and enasidenib, which are inhibitors that target mutated isocitrate dehydrogenase ( IDH ) 1 and 2, respectively, have been approved by the US Food and Drug Administration (FDA) for the treatment of IDH1/IDH2 -mutated R/R AML. Venetoclax, an inhibitor of B-cell lymphoma-2 ( BCL2 ), is widely used in the salvage treatment of R/R AML and has better therapeutic effects and controllable drug toxicity than traditional chemotherapy. In addition, chimeric antigen receptor (CAR) T-cell immunotherapy (targeting CD33, CD123, and CLL1) has achieved encouraging clinical response rates in phase I and phase II clinical trials for R/R-AML, and subsequent bridging HSCT has significantly improved patient survival.